2010
DOI: 10.1103/physrevstab.13.124702
|View full text |Cite
|
Sign up to set email alerts
|

Surface characterization of Nb samples electropolished with real superconducting rf accelerator cavities

Abstract: We report the results of surface characterizations of niobium (Nb) samples electropolished together with a single cell superconducting radio-frequency accelerator cavity. These witness samples were located in three regions of the cavity, namely at the equator, the iris, and the beam pipe. Auger electron spectroscopy was utilized to probe the chemical composition of the topmost four atomic layers. Scanning electron microscopy with energy dispersive x ray for elemental analysis was used to observe the surface to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…It has been shown that electropolished cavities can have niobium oxide crystals adhering to the interior surface [4]. In order to remove as many sites like this as possible, Fermilab has adopted the practice of allowing the electrolyte to circulate through the rotating cavity for 30 minutes after the polishing procedure has concluded.…”
Section: Post Electropolish Hf Rinsementioning
confidence: 99%
“…It has been shown that electropolished cavities can have niobium oxide crystals adhering to the interior surface [4]. In order to remove as many sites like this as possible, Fermilab has adopted the practice of allowing the electrolyte to circulate through the rotating cavity for 30 minutes after the polishing procedure has concluded.…”
Section: Post Electropolish Hf Rinsementioning
confidence: 99%
“…Chemical contamination of SRF cavities may occur by adsorption and absorption of any of the species present in the electropolishing solution. Evidence for oxygen, hydrogen, and sulfur has been found in several studies [45][46][47]. Oxygen contamination occurs by the oxidation processes discussed previously.…”
Section: Superconducting Radio-frequency Cavity Processingmentioning
confidence: 78%
“…Although many studies have been performed by the SRF community to understand the effect of polishing parameters on SRF cavity performance [34,40,47,57], as well as the mechanism and quality control of the process [38,[73][74][75][76][77][78][79]; the detailed chemistry remains elusive. Furthermore, simple inline process monitoring techniques are desired.…”
Section: Introductionmentioning
confidence: 99%
“…As the sampling depth of EDX analysis is approximately 1 m, the results were interpreted as the values for the bulk part of the catalysts [73]. The atomic concentration of Co, Ce and La (%) in the bulk part for each catalyst is very similar to the theoretical values for each component.…”
Section: Characterizationmentioning
confidence: 99%